PENERAPAN RELAKSASI GENGGAM JARI UNTUK MENURUNKAN NYERI POST OPERASI LAPAROTOMI PADA PASIEN KISTA COKELAT BILATERAL - Nia Rifti Ekawati; Apri Nur Wulandari; Wiwi Kustio Priliana (NHM PRESS, 2022)
Chocolate cyst or what is often called endometriosis is a functional endometrial condition that experiences cyclic bleeding. Treatment of endometriosis can be done by laparotomy. One of the nursing problems that often arises in post-laparotomy patients is severe pain or acute pain. Pain can affect various things, such as physical, behavioral, and also affect daily activities. Thus it is necessary to handle it so as not to give a negative influence. One of the relaxation techniques that can be used to reduce postoperative pain is the finger hold relaxation technique or often called the finger hold. This type of research is a case study research, which was conducted on 1 patient, namely Mrs. N. She is the first day postoperative laparotomy patient. The focus of this study is the application of finger-hold relaxation therapy to reduce post-laparotomy pain in chocolate cyst patients. Finger hold therapy is taught and carried out 2 times a day, at least 4 hours after administration of analgesic drugs, namely in the morning before taking the medicine and in the afternoon after lunch. Before and after being given the finger-hold relaxation intervention, the patient's perceived pain scale was measured. Measurement of the pain scale using the Verbal Descriptive Scale